2019
DOI: 10.2174/1568026618666181112143351
|View full text |Cite
|
Sign up to set email alerts
|

Natural-based Antibiofilm and Antimicrobial Peptides from Microorganisms

Abstract: New developments in antimicrobial peptides (AMPs) with antibiofilm properties are rapidly materializing. ABP works by inhibiting antibiotic resistant bacteria in the biofilm through nucleotide signaling molecules. Alternative Antibiotics Antimicrobial peptides and antibiofilm peptide (ABP) are new antibiotic molecules derived from microorganisms for the treatment of infections. The authors have discussed significance, limitations and trials of these antimicrobial peptides from bacteria, fungi, protozoa and yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…With limited availability of antibiotics as well as similarities in their mode of action, intensive research is directed toward the identification of novel and non-conventional therapeutics (Batoni et al, 2016; de la Fuente-Núñez et al, 2016; Haney et al, 2019). Recently, studies employing AMPs have gained momentum mainly due to the antimicrobial and antibiofilm activity along with their immunomodulatory properties (de la Fuente-Núñez et al, 2012, 2016; Yazici et al, 2018; Haney et al, 2019). EAEC causes chronic as well as persistent diarrhea that eventually damage the intestinal epithelium in human infants and young animals (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With limited availability of antibiotics as well as similarities in their mode of action, intensive research is directed toward the identification of novel and non-conventional therapeutics (Batoni et al, 2016; de la Fuente-Núñez et al, 2016; Haney et al, 2019). Recently, studies employing AMPs have gained momentum mainly due to the antimicrobial and antibiofilm activity along with their immunomodulatory properties (de la Fuente-Núñez et al, 2012, 2016; Yazici et al, 2018; Haney et al, 2019). EAEC causes chronic as well as persistent diarrhea that eventually damage the intestinal epithelium in human infants and young animals (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cationic antimicrobial peptides (AMPs) have emerged as an attractive target to source new antimicrobial technology solutions. AMPs are evolutionarily conserved molecules found in organisms ranging from prokaryotes to humans that have been heralded as promising alternatives to the currently available antibiotics (Yazici et al, 2018; Haney et al, 2019). Employing long chain amino acid sequences increase the output cost of peptides and thereby the cost of research; hence, synthetic short-chain cationic peptides with potential antimicrobial activity have been attempted (Anunthawan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is because that: (1) as a component of the innate immune system, production of AMPs by the host cells requires less time and energy than antibody synthesis by the acquired immunity; (2) these small molecule peptides can reach the target faster than immunoglobulins; and (3) some eukaryotes lack of lymphocyte-based immune system, such as insects mainly rely on the synthesis of a series of antibacterial compounds to remove invading microorganisms [ 16 ]. Since the first AMP was discovered in the American silkworm chrysalis, a large number of AMPs have been widely found in various organisms, including microorganisms [ 17 ], plants [ 18 ], invertebrates [ 19 ], fish [ 20 ], amphibians [ 21 ], reptiles [ 22 ], birds [ 23 ] and mammals [ 24 ].…”
Section: Natural Distribution Of Ampsmentioning
confidence: 99%
“…Besides, recent studies reported that intestinal microbiota served as a source of AMPs [ 31 , 32 ]. AMPs have also been found in fungi [ 17 ]. In addition, Copsin originated from Coprinopsis cinerea ( Mushroom ), has bactericidal effects on a variety of Gram-positive bacteria by interfering with the biosynthesis of the cell wall of pathogens, such as Enterococcus faecalis ( E .…”
Section: Natural Distribution Of Ampsmentioning
confidence: 99%
“…In addition, anti-angiogenesis [57,58] and suppression of metastasis [59] also contribute to tumor control by ACPs. Naturally occurring cationic peptides are present in every kingdom and phylum, including plants [60], animals [61], fungi [62] and bacteria [63], and they have also been identified in SV.…”
Section: Snake Venom-derived Antimicrobial and Anticancer Peptides (Smentioning
confidence: 99%